A Model of Capital Structure when Earnings are Mean-Reverting - Raymar, Steven (Journal of Financial and Quantitative Analysis, 1991)
A multiperiod model of optimal capital structure is developed under the assumption that earnings follow an autoregressive process. Firm value and leverage vary through time and, at each date, the firm achieves an optimal debt level that is a function of the full state contingent debt policy. The reversion parameter of the earnings series is shown to be positively related to various measures of variability and negatively related to leverage. If earnings processes are not homogeneous across firms, then standard earnings risk measures in capital structure studies do not adequately represent crosssectional differences in variability in firm value.